With skilful hand : the story of King David - Barnard, David T. (McGill-Queen's studies in the history of religion ;, 2004)
"In With Skillful Hand, one of the most complex figures of ancient scriptures is brought to life. David Barnard takes biblical stories and the formal recorded history about King David as the basis for a fictional account of the revered king's life. Structured as a series of letters from biblical characters, the book paints a portrait of the king as an elusive and complicated figure whose life challenges readers to recognize the inherent ambiguities of life."--Jacket